Giant intrathoracic goitre: The challenges. (2016) - Al Hashemy, Ahmed; Gallo, Ricardo; Shah, Mian Tahir; Al Faifi, Abdulla; Al Amir, Ahmad; Al Shraim, Mubarak; Ezzat, Nassr; Rabie, M. Ezzedien
Highlights: Huge intrathoracic goitre represents a real challenge to both the surgeon and the anaesthetist. The enormous size attained by such goitres is really impressive. In the case presented, it followed an incomplete thyroidectomy performed 14 years earlier. Massive bleeding should be anticipated and precautionary measures taken. Median sternotomy is the appropriate access in bilateral cases. Abstract: Intrathoracic goitre is defined as goitre in which at least 50% of the thyroid mass lies below the thoracic inlet. Here we report the case of a 43-year-old female, with history of left thyroid lobectomy 15 years earlier, who presented with dyspnoea. CT scan showed huge bilateral intrathoracic masses. Through median sternotomy, the masses were successfully excised, though with difficulty due to their hypervascular nature, along with completion thyroidectomy. Histopathology of the specimens showed multinodular goitre with no evidence of malignancy. The patient recovered well and one year after discharge, delivered a healthy baby.